ANALISIS POLA PERSEBARAN DAN KETERJANGKAUAN LOKASI SEKOLAH TERHADAP PEMUKIMAN DIKECAMATAN BATAUGA KABUPATEN BUTON SELATAN. - Mukhlis, Mukhlis; Musyawarah, Rahma (UNIVERSITAS NEGERI MAKASSAR, 2019)
This writing aims to analyze the distribution patterns and find out the affordability of the School's location to the settlements in the Batauga sub-district of South Buton Regency. The method used in this study is a quantitative descriptive method with Nearest Neighbor Analysis and baffer analysis. Data is obtained by survey and document review. The results showed 1) The pattern of distribution of School Locations in Batauga sub-district was calculated using the analysis of the nearest neighbor (Analysis Nearest Nigh) obtained T value = 0.26369, spatial pattern of School Location distribution in Batauga Subdistrict was Cluster pattern. 2). The results of Spatial Analysis using the Baffer function are the distribution of school locations in Batuaga Subdistrict, which have not fully served all villages in the subdistrict of Batauga. Educational facilities for junior high schools (SMP / MTs) are only able to serve 75%, namely Lawela Village, Lawela Seatan, Bandar Batauga, Busoa, Lakambau, Majapahit, Pogalampa, Mologina and Bola Village.